New species of Hemerodromia Meigen (Diptera: Empididae: Hemerodromiinae) associated with limestone karstic waters in Thailand - Plant, Adrian R. (Zootaxa, 2020)
Species descriptions are provided for five new species of Hemerodromia (H. aliaextriata sp. nov., H. deprimatura sp. nov., H. oretenebraea sp. nov., H. pairoti sp. nov. H. samoha sp. nov.). The new species have an apparently obligate association with calcareous streams, rivers and tufa formations in limestone karst landforms in Thailand. Hemerodromia menghaiensis Yang & Yang is here reported for the first time in Thailand.